PENGARUH MOTIVASI BELAJAR, MEMBACA KRITIS DAN CARA BELAJAR TERHADAP BERPIKIR KRITIS SISWA JURUSAN ADMINISTRASI PERKANTORAN SMK WIDYA PRAJA UNGARAN - Sofiya, Nila Raudlotus (Economic Education Analysis Journal, 2014)
Tujuanpenelitianiniadalahuntukmengetahuipengaruhmotivasi belajar, membaca kritis dan cara belajar terhadap berpikir kritis siswa jurusan Administrasi Perkantoran SMK Widya Praja Ungaran baik secara simultan maupun parsial. Populasidalampenelitianiniadalahseluruh siswa jurusan Administrasi Perkantoran SMK Widya Praja Ungaran tahun 2013/2014 sebanyak 265 siswa. Teknikanalisis data menggunakananalisisdeskriptifdananalisisinferensial. Hasilanalisismenunjukkanbahwapersamaangarisregresi linier bergandayaituÅ¶ = 20,409 + 0,086 (X1) + 0,078 (X2) + 0,082 (X3). Besarnyapengaruhsecarasimultanantaramotivasibelajar, aktivitasbelajardancarabelajarterhadapberpikirkritissiswayaitu 40,1%. Variabel yang memberikanpengaruh paling besarterhadapberpikirkritissiswaadalahmotivasibelajardanmembacakritiskeduanyamempunyaipengaruhsebesar 75,5%, sedangkancarabelajarberpengaruhlebihkecilyaitusebesar 73,4%.Â The purpose of this research is to find out whether there is an influence influence of Learning Motivation, Critical Learning of Critical Thinking Students majoring in Administration Offices SMK WidyaPrajaUngaran school year 2013/2014. The population in this research is the whole Office Administration majors SMK students WidyaPrajaUngaran year 2013/2014 of 265 students, then taken samples as much as 159 students. The data collecting method is questionnaire and documentation. The analysis data technique are descriptive and inferential analysis. Result of the analysis shows the multiple linear regression equivalent is Å¶ = 20,409 + 0,086 (X1) + 0,078 (X2) + 0,082 (X3). The result of the calculation shows the amount of the influence of effect of simultaneously between learning motivation, learning activities and how to learn critical thinking to students that 40.1%.Variables that provide the greatest influence of critical thinking students is the motivation to learn and the habit of reading both have the influence of a landslide 75.5%, while smaller influential way of learning which amounted to 73.4%. Â